Study of Competitive Setting in the Implementation of Cultural Advancement Policy in East Kalimantan Province - Apriani, Fajar; Hariati, Hariati (PINISI Discretion Review, 2025)
The policy of cultural advancement designed and implemented by the national and regional governments has an important role in facilitating and strengthening local cultural foundations and increasing the contribution of regional culture to the economy and social of the local community. Cultural practices are based on the daily life of the community in cultured, so that local governments are given the authority to establish and implement the policy of cultural advancement at the level of local government. The Provincial Government of East Kalimantan is carrying out cultural advancement based on the Regional Regulation of East Kalimantan Province Number 10 of 2022 through the Protection, Development, Utilization and Cultural Establishment. By Focus Group Discussion technique with East Kalimantan artists and cultural figures in collecting data and use of five forces analysis and SWOT analysis, this research examines descriptively competitive advantages of the Regional Government of East Kalimantan Province in the implementation of cultural advancement policy through the use of mixed methods. The results showed that the position of the East Kalimantan Provincial Government in the implementation of cultural advancement policy is the most profitable position, because it has strong internal power and good external opportunities to take advantage to these benefits. The right competition strategy to use is SO strategy, which can be done by cultural cooperation with partners, increasing the inventory of cultural advancement objects that have not been touched or recorded, and improve the quality of cultural advancement programs that have been carried out. These efforts are made to increase the involvement and participation of other cultural advancement of the non-government elements for the success of the better implementation of East Kalimantan cultural advancement.